Advanced imaging in acute ischemic stroke: an updated guide to the hub-and-spoke hospitals. Issue 1 (February 2022) - Sharobeam, Angelos; Yan, Bernard
Abstract : Purpose of review: The purpose of this review is to summarize the role of the hub-and-spoke system in acute stroke care, highlight the role of advanced imaging and discuss emerging concepts and trials relevant to the hub-and-spoke model. Recent findings: The advent of advanced stroke multimodal imaging has provided increased treatment options for patients, particularly in rural and regional areas. When used in the hub-and-spoke model, advanced imaging can help facilitate and triage transfers, appropriately select patients for acute therapy and treat patients who may otherwise be ineligible based on traditional time metrics. Recent, ongoing trials in this area may lead to an even greater range of patients being eligible for acute reperfusion therapy, including mild strokes and patients with large core infarct volumes. Summary: Integration of advanced imaging into a hub-and-spoke system, when complemented with other systems including telemedicine, improves access to acute stroke care for patients in regional and rural areas.